Induced Resistance Mechanism of Twisted Disease Suppression of Shallot by Bacillus spp. - Elfrida Indriani Reno Wulan; Arif Wibowo; Tri Joko; Ani Widiastuti (Universitas Gadjah Mada, 2022)
Plant Growth Promoting Rhizobacteria has been known for its ability to induce plant resistance on shallot against twisted disease. Its ability as a bioprotectant agent is estimated to be comparable to the efficacy of Trichoderma which is currently widely used as a biological control agent.. This study aims to determine the content of jasmonic acid, salicylic acid, peroxidase, and disease suppression in shallot by application of Bacillus velezensis B-27, Bacillus cereus RC76, and application with combination of both rhizobacteria. The application was carried out with tuber dipping for 30 minutes in each treatment with a bacterial density of 108 CFU mL-1. Application using Trichoderma was used as the comparison treatment, and the control plot was not given any treatment. Pathogen inoculation was carried out simultaneously as planting using Fusarium acutatum with a spore density of 106 CFU mL-1. The jasmonic and salicylic acids content was measured using the High-Performance Liquid Chromatography method, and the peroxidase content was determined using the spectrophotometric method. Disease suppression was measured at 10-day intervals. The results showed that treatment with Bacillus cereus RC76 increased jasmonic and salicylic acid levels, while application with Bacillus velezensis B-27 showed the highest level of peroxidase. Treatments with Bacillus spp. were able to suppress twisted disease by 72.2% to 100%. This study demonstrated that application Bacillus spp. suppressed twisted disease on shallot and increased the jasmonic and salicylic acid content as induced resistance mechanism against pathogens.